Preparation of β-lactoglobulin-derived tryptophan peptide and its effect on anxiety-like behaviors in Zebrafish - Zhu, Xiping; Xie, Dan; Zhu, Qiong; Li, Yufeng; Cui, Chun (Frontiers in Nutrition, 2023)
This study aimed to obtain three Trp-containing peptides from β‐lactoglobulin and study their effects on anxiety-like behaviors in zebrafish. The anxiety-like behaviors of zebrafish were reduced after two weeks of administrated of β-lactoglobulin Trp peptides (LAWP), VAGTWY, VAGTW and GTW (concentration of 56 μg/mL or 500 μg/mL). As an index of serotonergic activity, we assessed the enhancing abilities of 5-HT synthesis. The treatment remarkably enhanced the 5-HT synthesis by upregulation of Trp concentration and Trp hydroxylase activation. In addition, this paper further validated the anti-anxiety effects of whey protein hydrolysate with a high Trp index in animal and the experimental results were consistent with those reported in previous studies. Our results showed that β-lactoglobulin Trp peptides ingestion has a significant anti-anxiety effect as evidenced by the increasing Trp concentration, TPH activation and 5-HT level compared to the control group, with the VAGTW being the more effective.